Solving the Equation: (a1)(a2)+(a3)(a+4)(2a^2+5a34)=7a+24
This article will guide you through the steps of solving the given equation.
Expanding the Equation
The first step is to expand the equation by multiplying out the brackets and combining like terms.

Expand (a1)(a2): (a1)(a2) = a²  2a  a + 2 = a²  3a + 2

Expand (a3)(a+4): (a3)(a+4) = a² + 4a  3a  12 = a² + a  12

Rewrite the equation: a²  3a + 2 + a² + a  12  (2a² + 5a  34) = 7a + 24

Simplify the left side: 2a²  7a + 24  2a²  5a + 34 = 7a + 24

Combine like terms: 12a + 58 = 7a + 24
Solving for 'a'
Now we have a simpler equation with only one variable. Let's solve for 'a'.

Add 7a to both sides: 5a + 58 = 24

Subtract 58 from both sides: 5a = 34

Divide both sides by 5: a = 6.8
Conclusion
Therefore, the solution to the equation (a1)(a2)+(a3)(a+4)(2a^2+5a34)=7a+24 is a = 6.8.